Experts’ perceptions on the decriminalization of drug use for criminal justice and health in Gauteng province - Netshivhumbe, Mukhethwa (University of the Witwatersrand, Johannesburg, 2021)
Drug abuse is an ongoing global challenge with the prevalence of drug abuse and drug use disorders increasing significantly in recent years. South Africa like the rest of the world is not immune to the drugs scourge. The Department of Social Development (2020) stated that South Africa has become a consumer, producer, and transit country for drugs. Growing evidence suggest that criminalising drug use has no effect in reducing the problem in South Africa, hence the need to start thinking about new methods to deal with the challenge, regardless of how radical the new methods might seem. Emphasis should be placed on evidence based public health and social justice approaches. Decriminalisation is a phenomenon that is gaining momentum worldwide but can be considered radical now, since it requires extensive overhaul of any country’s illegal drugs’ policy. This study attempted to explore the perceptions of the experts in the field of substance abuse regarding the efficacy of decriminalising drug possession and use in Gauteng province, SA. Qualitative methodology with exploratory nature was utilized in this study. Interpretivism as the underlying research method was applied for this study. A basic interpretative study research design was adopted, as the focus was the building of this knowledge. Purposive sampling method was used to select participants of this study. Data were collected using semi-structured interviews. Interviews were conducted face to face and using virtual platform (Zoom). Data were transcribed and analysed using thematic analysis. Data were presented focusing on the themes and emerged themes stemming from the purpose and objective of the study. This study has established different thoughts on the subject matter of decriminalisation of drug use. The majority (11 out of 15) of participants were in support of decriminalization of drug use. Their views were that the current approaches for combating drug problem have not yielded positive results hence a need to explore an alternative approach. Those against the decriminalisation of drug use were concerned that decriminalisation will results in an increase in drug use and drug dealers will flock into the country to sell drugs. They further expressed that the scourge of drug abuse is fuelled by social ills in the country, not criminalisation of drug use, therefore the country should address social problems and the drug problems may be reduced.
A research report submitted to the Faculty of Management, University of the Witwatersrand in requirement for the degree of Master of Management in the Field of Governance specializing in Monitoring and Evaluation, Johannesburg 2021
Keywords: Drug abuse; Drug use disorders; Drugs; Decriminalizatio; Criminal justice; UCTD; SDG-16: Peace, justice and strong institutions